2020
DOI: 10.1002/lsm.23283
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Ultrapulsed CO2 Laser in Chronic Wounds

Abstract: Background and Objectives Chronic wound repair is a major problem in wound treatment. Recently, several studies have suggested that carbon dioxide (CO2) laser can be used to improve the healing of chronic wounds. The aim of the present study was to preliminarily investigate the efficacy of laser debridement in treating chronic wound through a comparison of traditional instrument/surgical debridement with the ultrapulsed CO2 laser debridement in terms of wound healing, wound infection control, and wound blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is also correlated with superior wound status and causes no adverse events. 23,26,27 CO 2 laser employs high levels of energy to vaporize biological tissues. Its wavelength is 10,600 nm for targeting water in the superficial tissues and rarely scatters or penetrates, depositing energy to a precise depth below the surface of the skin without affecting the deeper tissues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is also correlated with superior wound status and causes no adverse events. 23,26,27 CO 2 laser employs high levels of energy to vaporize biological tissues. Its wavelength is 10,600 nm for targeting water in the superficial tissues and rarely scatters or penetrates, depositing energy to a precise depth below the surface of the skin without affecting the deeper tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, CO 2 laser may play an important role in controlling local infection in the wound bed. Jiang et al 23 found that CO 2 laser treatment reduces bacterial culture‐positive rate more than routine debridement. In a prospective study of 60 patients, Juri et al 21 also demonstrated a lower infection rate in a CO 2 laser group than a conventional surgery group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations